2013
DOI: 10.1074/mcp.m112.025775
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals the Induction of Mitophagy in Tumor Necrosis Factor-α-activated (TNFα) Macrophages

Abstract: Macrophages play an important role in innate and adaptive immunity as professional phagocytes capable of internalizing and degrading pathogens to derive antigens for presentation to T cells. They also produce pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-␣) that mediate local and systemic responses and direct the development of adaptive immunity. The present work describes the use of label-free quantitative proteomics to profile the dynamic changes of proteins from resting and TNF-␣-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 65 publications
1
26
1
Order By: Relevance
“…The RAW 264.7 macrophage cell line (ATCC), the H-2K b RAW cell line (Bell et al, 2013), and COS7 cells (ATCC) were cultured in DMEM (10% [v/v] fetal calf serum [FCS], penicillin [100 units/ml], and streptomycin [100 mg/ml]). The b-galactosidase-inducible HSV gB/K b -restricted HSV-2.3.2E2 CD8+ T cell hybridoma (2E2) was kindly provided by F. Carbone (University of Melbourne).…”
Section: Methodsmentioning
confidence: 99%
“…The RAW 264.7 macrophage cell line (ATCC), the H-2K b RAW cell line (Bell et al, 2013), and COS7 cells (ATCC) were cultured in DMEM (10% [v/v] fetal calf serum [FCS], penicillin [100 units/ml], and streptomycin [100 mg/ml]). The b-galactosidase-inducible HSV gB/K b -restricted HSV-2.3.2E2 CD8+ T cell hybridoma (2E2) was kindly provided by F. Carbone (University of Melbourne).…”
Section: Methodsmentioning
confidence: 99%
“…In order to be presented on MHC class I molecules, antigens must be processed to peptides, classically by the proteasome. However, it has recently been shown that antigens can be processed via the lysosome, following autophagy or mitophagy [9,10]. Matheoud et al now show that, in addition, mitochondrial proteins can be transported to the lysosome by MDVs for subsequent presentation on MHC class I molecules.…”
mentioning
confidence: 99%
“…In recent years, the cell line has also been used extensively in proteomics experiments including a large‐scale proteome 10, phagosome proteomics 4, 8, 11, responses to cytokines 12, 13, and identification of DNA receptors 14.…”
mentioning
confidence: 99%